Correction: Data from 617 Healthy Participants Performing the Iowa Gambling Task: A "Many Labs" Collaboration. Issue 1 (4th December 2015) - Steingroever, Helen; Davis, Hasker; Fridberg, Daniel J.; Horstmann, Annette; Kjome, Kimberly L.; Kumari, Veena; Lane, Scott D.; Maia, Tiago V.; McClelland, James L.; Pachur, Thorsten; Premkumar, Preethi; Stout, Julie C.; et al.
This article details a correction to the article: Steingroever, H. et al., (2015). Data from 617 Healthy Participants Performing the Iowa Gambling Task: A "Many Labs" Collaboration. Journal of Open Psychology Data. 3:e5. DOI:http://doi.org/10.5334/jopd.ak